High photo‐conversion efficiency in double‐graded Cu(In, Ga)(S, Se)2 thin film solar cells with two‐step sulfurization post‐treatment. (27th September 2016) - Kim, Gee Yeong; Yang, JungYup; Nguyen, Trang Thi Thu; Yoon, Seokhyun; Nam, Junggyu; Lee, Dongho; Kim, Dongseop; Kwon, Minsu; Jeon, Chan‐Wook; Kim, Yoon‐Koo; Lee, Seung‐Yong; Kim, Miyoung; et al.
Abstract: Sulfur is extensively used to increase the bandgap of Cu(In, Ga)(S, Se)2 (CIGSSe) solar cells and to improve the open circuit voltage ( VOC ) in order to optimize the characteristics of the devices. This study uses a sulfurization process to obtain a double‐graded bandgap profile. Selenization was carried out on Cu(In, Ga) precursors, followed by one sulfurization process or two consecutive sulfurization processes on top of the CIGSe absorber layer surface. The optimum two‐step sulfurization process provides an increase of VOC of 0.05 V and an improvement of conversion efficiency of 1.17%. The efficiency of the 30 × 30 cm 2 monolithic module, which has 64 CIGS cells connected in series (aperture area: 878.6 cm 2 ), is 15.85%. The optical and electrical properties of the phase and the work function distribution were investigated using the depth profiles of the absorber layer as a function of the sulfurization conditions. The CIGSSe thin film formed by two‐step sulfurization with a high sulfur concentration exhibits a single work function peak, better crystallinity, and higher conversion efficiency than those of the thin film formed by two‐step sulfurization at low sulfur concentration. In terms of the Raman spectra depth profile, the phase areas for the CIGSSe thin film that underwent the optimized high sulfur concentration two‐step‐sulfurization appeared to have less of Cu2‐x Se phase than that with low sulfur concentration. Consequently, surface and interface phase analysis is an essential consideration to improve cell efficiency. Copyright © 2016 John Wiley & Sons, Ltd. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This study uses a sulfurization process to obtain a double‐graded bandgap profile. The CIGSSe thin film that underwent a two‐step sulfurization process exhibited a single work function peak, better crystallinity, and high conversion efficiency relative to the thin film that underwent a one‐step sulfurization process.